Amorphous Cu-added/SnOx/CNFs composite webs as anode materials with superior lithium-ion storage capability. Issue 51 (6th May 2015) - Chi, Cheng; Lan, Jinle; Sun, Jiangman; Liu, Yuan; Yu, Yunhua; Yang, Xiaoping
Abstract : Cu-addition plays a significant role in restricting the aggregation of Sn particles during a continuous charge–discharge progress and improving the cycling stability of SnO x /CNFs electrode. Abstract : Amorphous Cu-added tin oxides/carbon nanofiber (Cu-added SnO x /CNFs) composite webs used for lithium-ion battery anode materials are prepared by an electrospinning technique and subsequent thermal treatment. The Cu-doped SnO x particles are uniformly distributed in the CNFs and maintain the original morphology after long-term cycling. In a controlled experiment, SnO x -20%Cu/CNFs with an atomic ratio of Cu : Sn = 0.2 shows the highest electrochemical performance with a high reversible capacity of 743 mA h g −1 at a current density of 200 mA g −1 and an excellent rate capacity of 347 mA h g −1 at 5 A g −1 . Moreover, the composite electrode exhibits an outstanding long-term cycling performance at 2 A g −1 even after 1000 cycles. The superior reversible lithium-ion storage capability is attributed to the uniform dispersion of the Cu2 O and ultrafine SnO x particles in CNFs as well as the Cu-addition effects such as promoting electron transport and Li + diffusion, preventing Sn from aggregation during cycling, and improving the reversibility of Sn back to SnO x in the recharge process.